Assessment Evaluation Using Solo Taxonomy for Measuring Levels of Critical Thinking Skills: PYP International Baccalaureate Case Study - Triana, Hana; Abustang, Perawati Bte; Utomo, Erry; Rakhman, Gumgum Gumelar Fajar; Fahrurrozi, Fahrurrozi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to evaluate and document learning outcomes using the SOLO taxonomy model as an indicator of learning outcomes. Higher order thinking skills towards critical thinking elements. This research uses case studies with mixed methods qualitative and quantitative research methods with documentation research instruments of data analysis. The research sample was conducted in 2 4th grade elementary schools in Jakarta which implemented the IB (International Baccalaureate) curriculum by using the results of the SOLO taxonomy assessment. Data collection is done by interview method, analysis of the researched data documentation on critical thinking skills using the SOLO Taxonomy framework in the learning process and the level of assessment descriptors as scores or grading student report card assessments. The SOLO taxonomy descriptor level of the highest level of thinking skills is Extended Abstract with an assessment descriptor value of 5 and the lowest descriptor value of 3 (multi-structural) for reporting learning outcomes based on the achievement of student learning outcomes on understanding the concept of knowledge. Stages of students’ critical thinking from not knowing to the level of understanding of concepts/learning outcomes related to real life. So it can be concluded that the results of this case study research can be used as an evaluation of the reporting of learning outcomes on critical thinking skills in the learning process and documentation of reporting assessments of learning at the elementary school level. The higher the students’ critical thinking skills in understanding the concept of learning outcomes, the students reach the Higher Order Thinking Skills stage or the high-level skills needed in 21st century learning in solving real-life cognitive problems.